2015
DOI: 10.4049/jimmunol.1500386
|View full text |Cite
|
Sign up to set email alerts
|

Bee Venom Phospholipase A2, a Novel Foxp3+ Regulatory T Cell Inducer, Protects Dopaminergic Neurons by Modulating Neuroinflammatory Responses in a Mouse Model of Parkinson’s Disease

Abstract: Foxp3-expressing CD4+ regulatory T cells (Tregs) are vital for maintaining immune tolerance in animal models of various immune diseases. In the present study, we demonstrated that bee venom phospholipase A2 (bvPLA2) is the major BV compound capable of inducing Treg expansion and promotes the survival of dopaminergic neurons in the 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine mouse model of Parkinson’s disease. We associated this neuroprotective effect of bvPLA2 with microglial deactivation and reduction of CD4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
80
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 77 publications
(88 citation statements)
references
References 52 publications
4
80
0
2
Order By: Relevance
“…Our previous studies reported that bee venom treatment successfully protects various immune disorders by increasing Treg populations [9,26]. Furthermore, we found that PLA2 is the active compound in bee venom capable for modulating the Treg populations, both in vitro and in vivo [9,10,11].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Our previous studies reported that bee venom treatment successfully protects various immune disorders by increasing Treg populations [9,26]. Furthermore, we found that PLA2 is the active compound in bee venom capable for modulating the Treg populations, both in vitro and in vivo [9,10,11].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we found that PLA2 is the active compound in bee venom capable for modulating the Treg populations, both in vitro and in vivo [9,10,11]. PLA2 from bee venom belongs to group III secreted PLA2 (sPLA2) enzymes, which play important roles in a wide range of cellular functions, including phospholipid metabolism, signal transduction, and inflammatory and immune responses [27].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations